Reducing of Non-Productive Heat Losses in Energy Generation - Demchenko, Vladimir Georgievich; Konyk, Vasilyevna (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2020)
The article is devoted to the analysis of non-productive losses in the generation of thermal energy. The causes of heat losses and their localization on the station equipment, technological pipeline and at unbalance of technological processes are established. As a result of the analysis, recommendations were given for the joint use of nuclear power plants (NPPs) or thermal power plants (TPPs) with available renewable energy sources (RES), using thermal storage systems, which will balance the system "generation - transportation - consumption". The use of stationary and mobile heat accumulators in the generation of RES, secondary thermal energy (TER) will reduce heat loss, use low-potential sources, which will relieve service equipment, reduce fuel consumption (FER) and harmful emissions into the environment. Also, it is recommended to conduct a full energy audit of station equipment and pipelines. Implement replacement of technically obsolete equipment with low efficiency, replace piping and insulation. Update the automation system, introduce a process scheduling system. Balance technological processes.